Ketokohan Dan Sumbangan Ustaz Che Yahaya Bin Daud Dalam Bidang Tarannum Al-quran Di Malaysia - Anuar Hasin (Universiti Sains Islam Malaysia, 2024)
This study discusses on the scholarship and contributions of Ustaz Che Yahaya bin Daud in the field of tarannum towards the people in the state of Kelantan in particular and Malaysia in general. The objective of this study is to explore in detail the specialty and distinctive quality of Ustaz Che Yahaya bin Daud in the field of Quranic reading. The researcher investigates Ust Che Yahya’s involvement in the field of tarannum as well as to identify the method he uses in delivering tarannum knowledge to qari and qariah in Malaysia. The author uses two main methods to collect important data for this study, which are interviews and observation methods. The researcher found that the Ustaz Che Yahaya bin Daud has contributed significantly to the community in the field of tarannum and Quranic studies not only in the state of Kelantan, but also throughout Malaysia. The contributions included discovering new talents and improving the quality of existing qari and qariah. The study also found that Ustaz Che Yahaya bin Daud was greatly influenced by the reading of Syeikh Mustafa Ismail from Egypt where he has applied the Syeikh’s approaches in his teaching and learning method.